2007
DOI: 10.1002/ijc.23073
|View full text |Cite
|
Sign up to set email alerts
|

Oldest known case of metastasizing prostate carcinoma diagnosed in the skeleton of a 2,700‐year‐old Scythian king from Arzhan (Siberia, Russia)

Abstract: To determine whether a 2,700-year-old tumor can be reliably diagnosed using microscopic and proteomic techniques and whether such prostate carcinomas show the same morphological pattern at the micro-level as modern-day carcinomas, this case was investigated. A 40-50-year-old Scythian king who lived during the Iron Age in the steppe of Southern Siberia (Russia) suffered from macroscopically visible osteoblastic and osteoclastic lesions throughout his entire skeleton. Macro-morphological (macroscopy, endoscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 21 publications
1
42
0
1
Order By: Relevance
“…For example, ancient proteins have revealed past diseases such as osteogenic sarcoma and prostate carcinoma [17,79]. Scott et al  [80] reported that osteocalcin analysis is promising for detecting stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ancient proteins have revealed past diseases such as osteogenic sarcoma and prostate carcinoma [17,79]. Scott et al  [80] reported that osteocalcin analysis is promising for detecting stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a biomolecular approach to diagnosis in addition to osteological examination can be beneficial [14]. Recently, proteomic profiling of human tumors has provided a better understanding of the molecular pathogenesis of neoplastic diseases and has identified novel biomarkers for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Strouhal et al, 1996); Russia (e.g. Schultz et al, 2007); Slovakia (e.g. Š efčáková et al, 2001), Italy (e.g.…”
Section: Malignancy In Paleopathological Recordmentioning
confidence: 98%